2021
DOI: 10.1037/ort0000519
|View full text |Cite
|
Sign up to set email alerts
|

Welcoming places: Perspectives of individuals with mental illnesses.

Abstract: There are many factors that influence community participation of individuals with serious mental illnesses. Research often focuses on barriers to participation. This study, however, takes a different approach, by exploring features of community locations considered welcoming by individuals with serious mental illnesses. This is important because welcoming environments are more likely to promote community participation. Using a survey approach, 75 participants were asked to identify and describe locations where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The art and cultural activity deemed to be important by the greatest number of individuals in our SMI sample was the library (70%), and yet, 57% of those individuals reported that they had not done it once in the past month (breadth) and 68% reported that they are not doing it as much as they would like (sufficiency). Other research has found that very few people with SMI mentioned libraries as a public space where they felt welcomed (Snethen et al, 2021). Therefore, it is plausible that stigma plays a role in decreased library attendance and possibly engagement in other areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The art and cultural activity deemed to be important by the greatest number of individuals in our SMI sample was the library (70%), and yet, 57% of those individuals reported that they had not done it once in the past month (breadth) and 68% reported that they are not doing it as much as they would like (sufficiency). Other research has found that very few people with SMI mentioned libraries as a public space where they felt welcomed (Snethen et al, 2021). Therefore, it is plausible that stigma plays a role in decreased library attendance and possibly engagement in other areas.…”
Section: Discussionmentioning
confidence: 99%
“…Public libraries are always free to attend, perhaps more research needs to be done to understand why this important area is not being done enough. In locations where stigma may be an issue, trainings could be conducted to promote awareness about mental illness (Bowman et al, 2020; Morgan et al, 2021) and to create more inclusive environments (Snethen et al, 2021). Given that stigma can also be associated with increased social anxiety (Lysaker et al, 2010), it may be beneficial to find events or locations that are less crowded or that offer accommodations for people with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Bearing all this in mind, we find that it is important that the framework for places like Lts is visible in the community so that people who need healthcare will see the health-promoting effect such centres have. Places that are welcoming and promote participation in the community are found to contribute to health and well-being for people struggling with their mental health [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings show that when people do activities, they know they manage and enjoy doing, a feeling of joy is created, and even greater joy is experienced from sharing the activity with others. Engagement in different activities makes meaningful social roles visible and is described by Snethen et al [ 50 ] as a desirable feature and important opportunity within community locations.…”
Section: Discussionmentioning
confidence: 99%
“…These naturally occurring, causal relationships in the community, or “distal relationships,” are helpful for individuals’ community integration and recovery (Kriegel et al, 2020; Townley et al, 2013). In addition, people living with mental illnesses have identified religious organizations, restaurants, coffee shops, parks, libraries, and cultural centers as places in the community that are particularly welcoming (Snethen et al, 2021). Identifying gaps in resources will serve as a starting point for facilitating connection to any needed resources, while identifying strengths in resources will serve as support systems for the client as they strive toward their identified functional goals.…”
Section: Developing a Shared Understanding Of One’s Goals And Problemsmentioning
confidence: 99%